HUBUNGAN PENDEKATAN SAINTIFIK DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR - nurbaya nurbaya; Yusminah Hala; Muhammad Wiharto; Firdaus Daud (UNM Journal of Biological Education, 2018)
The objectives of the research are to discover  (i) the relation between scientific approach and learning motivation simultaneously toward students’ learning results at Public Junior High School in Maros District; (ii) the relation between scientific approach and learning results of the students at Public Junior High School in Maros District; (iii) the relation between learning motivation and learning results of the students at Public Junior High School in Maros District. The research is ex post facto in a form of multiple regression.  The data collecting techniques employed documentation and learning motivation questionnaire. The result of the research reveal (i) there is a positif and significant relation between scientific approach and learning motivation simultaneously toward students’ learning results at Public Junior High School in Maros District; (ii) there is a positif and significant relation between scientific approach and learning results of the students at Public Junior High School in Maros District; (iii) there is a positif and significant relation between  learning motivation and learning results of the students at Public Junior High School in Maros District.